Synthesis, Structural Characterization, and Hydrogen Release of Al-Based Amidoboranes Derived from MAlH4 (Li, Na)-BH3NH2CH2CH2NH2BH3 - Ting Zhang; Xiao Li; Hai-Wen Li; Michel Devillers; Yaroslav Filinchuk (Molecules)
Over the past two decades, the high hydrogen content and favorable dehydrogenation conditions of multi-metallic amidoboranes have gained significant attention for their potential in hydrogen storage. Among them, Al-based complex hydrides have shown promise because of their high polarizing power, light weight, and abundant natural presence. In this work, we successfully synthesized two novel tetrahedrally coordinated Al-based amidoboranes, namely, Li[Al(BH3NHCH2CH2NHBH3)2] and Na(THF)[Al(BH3NHCH2CH2NHBH3)2], using BH3NH2CH2CH2NH2BH3 (EDAB) as a precursor. The structure of Na(THF)[Al(BH3NHCH2CH2NHBH3)2] was determined through modeling based on synchrotron powder X-ray diffraction. Additionally, the formation of the Al-N bond in Li[Al(BH3NHCH2CH2NHBH3)2] and Na(THF)[Al(BH3NHCH2CH2NHBH3)2] was confirmed with IR spectra. Na(THF)[Al(BH3NHCH2CH2NHBH3)2] is more stable in air than Li[Al(BH3NHCH2CH2NHBH3)2]. Importantly, thermal gravimetric analysis and mass spectroscopic characterization confirmed that both compounds release hydrogen without the presence of ammonia, diborane, or ethylenediamine. Our work represents the first example of Al-based amidoboranes with chelation coordination geometry, which provides an essential foundation for understanding the relationship of complex multi-metallic amidoboranes in terms of synthesis, structure, and properties.